1977
DOI: 10.1161/01.res.40.5.445
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stroke volume and velocity of ejection on end-systolic pressure of canine left ventricle. End-systolic volume clamping.

Abstract: To study the effects of contraction mode on ventricular end-systolic pressure-volume relationship, we compared the end-systolic pressure of isovolumic contraction with that of ejecting contraction at an identical end-systolic volume. The left ventricle of excised cross-circulated canine hearts was fitted with a water-filled balloon. The balloon was connected to a hydraulic pump that allowed the ventricle to contract to a preset constant end-systolic volume (19-37 ml) from a variable end-diastolic volume. At ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 33 publications
(17 reference statements)
3
15
0
Order By: Relevance
“…This produces a depression of end-systolic pressure when end-diastolic volume is large compared with the value that would be expected from the ESPVR obtained with small end-diastolic volumes. This agrees with results obtained in isolated hearts by Suga and Yamakoshi,6 who showed that ESPVR is affected by ejection, particularly when stroke volume is large. Kass and Maughan'8 recently insisted on the difference between the true Emax (obtained in isolated hearts from differently loaded beats synchronized in time) and ESPVR obtained in the in situ heart, which can lead to Emax significantly steeper than Ees.…”
Section: Preload Dependence Of Espvrsupporting
confidence: 93%
“…This produces a depression of end-systolic pressure when end-diastolic volume is large compared with the value that would be expected from the ESPVR obtained with small end-diastolic volumes. This agrees with results obtained in isolated hearts by Suga and Yamakoshi,6 who showed that ESPVR is affected by ejection, particularly when stroke volume is large. Kass and Maughan'8 recently insisted on the difference between the true Emax (obtained in isolated hearts from differently loaded beats synchronized in time) and ESPVR obtained in the in situ heart, which can lead to Emax significantly steeper than Ees.…”
Section: Preload Dependence Of Espvrsupporting
confidence: 93%
“…The ventricular end-systolic pressure-volume relation was, however, no longer unique when ventricular stroke volume was varied. In a similar set of experiments, the endsystolic pressure at a given end-systolic volume was dependent both on stroke volume and ejection velocity (Suga and Yamakoshi, 1977). In these experiments, however, the pattern of ejection flow and, therefore, also the pattern of ventricular loading was different as peak velocity occurred much later in systole.…”
Section: Discussionmentioning
confidence: 85%
“…However, a similar magnitude of change in the end-systolic pressure can be ascribed to a change in the contractile state if the end-systolic, end-diastolic, and hence stroke volume and ejection fraction are unchanged as in run IV. Suga and Yamakoshi (1977) performed a similar study concerning the effects of ejection fraction and of the onset and velocity of ejection on end-systolic pressure. There are obvious differences between the two studies in the effects of changes in the onset and velocity of ejection on the end-systolic pressure.…”
Section: Discussionmentioning
confidence: 99%